ANALISIS KEBUTUHAN APARATUR PEMERINTAH JABATAN FUNGSIONAL DI INSPEKTORAT KOTA SINGKAWANG - Khatizah E.42009088 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
Thesis writing is intended to determine the factors that led to the ineffectiveness of the number the Functional Government Apparatus at Inspectorate Singkawang. The title of of this thesis concerns raised by the availability of the number the Functional Government Apparatus who have not been effective based on workload the achievement of targets in the inspection object.This research uses a model of the kind of exploratory qualitative descriptive research. The research was carried out by four research steps, namely a preliminary investigation (presurvey), making research plan (Proposed Research), secondary data collection and primary data which is then analyzed on the same day after data collection in the field (interviews or observation), and a research report (Thesis). Research sites in Singkawang. The research subject is Singkawang Government needs analysis related to Analysis of Functional Government Apparatus Need, Inspectorate Singkawang, Functional Government Apparatus.The conclusion of this research is the ineffectiveness of the Functional Government Apparatus amount as the imbalance between workload given to the number of Functional Government Apparatus with working time used by the apparatus. For the policy recommendation is to consider the policy in terms of the assignment inspection by officials, hasten creation of Functional Workload Analysis, and arrange the apparatus need to be filed in the formation of the Functional Government Apparatus acceptance. Keywords : Analysis of Need, Functional Government Apparatus, Effective.